STANDARDISATION OF SERVICES AS PREREQUISITE FOR OVERCOMING THE DISCREPANCY BETWEEN THE EXPECTED AND THE PERCEIVED QUALITY IN HOTEL BUSINESS - Vujko, Aleksandra; Petrović, Marko D; Gajić, Tamara; Jovanović, Vladimir; Jovanović, Slavica (International Journal of Economic Practice and Policy, 2018)
Standardization of services in the hotel industry is the key to the success of any hotel business. More importantly, the primary goal of implementing standards in the hotel industry represents the tendency of hoteliers to preempt any discrepancy between the expected and the perceived quality of hotel services. Research model was developed based on SERVQUAL model while a survey was conducted among 211 guests in three hotels in Novi Sad during 2016. The study concluded that the discrepancy is extremely negative, and that the best way to overcome the gap is the implementation of standards in the hotel business.best way to overcome the gap is the implementation of standards in the hotel business.